Estimasi Jumlah Murid Baru Menggunakan Metode Forecasting - Dwi Harini; Lilia Sinta Wahyuniar (Pendidikan Matematika STKIP Kusuma Negara, 2021)
Of the many forecasting methods or forecasting, the Linear Regression Method can be used to predict or predict the number of new students or students in the new academic year at the Islamic Junior High School